Isolasi dan Karakterisasi Senyawa Capsaicin dari Cabai Rawit (Capsicum Frutescens L.) sebagai Bahan Aditif Pangan dengan Metode Ekstraksi Sokletasi - Khairani, Khairani; Adriana, Adriana; Pardi, Pardi (Jurnal Teknologi, 2024)
Cayenne peppers have quite high economic value, but cayenne peppers are a type of fruit that is easily damaged by freezing. Therefore, proper post-harvest handling is needed, one of which is by extracting the spicy compounds in chilies. This research aims to increase the yield of capsaicin, determine the effect of drying time on the quality of capsaicin and crystallize capsaicin extract. The drying time used was 8; 10; 12; 14 hours. Cayenne pepper extraction was carried out using the soxhletation method at a temperature of 80°C and ethanol as a solvent, with a ratio of 1:7; 1:8; 1:9; 1:10 (w/v), after the extraction process, evaporation is carried out to obtain a concentrated extract of cayenne pepper. After obtaining a concentrated extract of capsaicin, a crystallizing compound, namely maltodextrin, is added to obtain capsaicin crystals. Drying time of 14 hours produces the lowest air content, namely 13.5%. The capsaicin yield was 22.17%. The capsaicin compound is insoluble in water but soluble in chloroform. The spiciness level of capsaicin is quite spicy with a value of 12,551.56 SHU. The capsaicin composition detected through GCMS analysis was 56.32% at a retention time of 42.87 minutes containing 563.2 ppm capsaicin. The research results showed that drying time and solvent ratio had an effect on the capsaicin yield, the longer the drying time and the greater the amount of solvent, the greater the capsaicin yield.